PROCESSING CONDITIONS ON PERFORMANCE OF MANUALLY OPERATED TOMATO SLICER - O. S, Kamaldeen; J. S, Abioye; E. F a, Awagu; A. A, Isiaka (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2017)
Modified tomato slicing machine and the old tomato slicing machine were evaluated to study the effects of tomato firmness on the slicing process of the two machines. The data from evaluation was analyzed using descriptive test analysis and these were compared using student t-test to know the level of improvement achieved on the new machine. The results show that tomato firmness has effect on slicing efficiency and output capacity of the machine. The modified slicer gave the best slicing performance of 94% with mature green tomato and also gave the highest output capacity of 3.09 kg/hr with ripe tomato while the old machine gave the best slicing performance of 65% with mature green tomato and as well gave the highest output capacity of 1.30 kg/hr with ripe tomato.